Enterprise Risk Management Practices and Performance of Microfinance Institutions in Makurdi Metropolis, Benue State-Nigeria - Emmanuel Lubem Asenge; Douglas Kumawuese Iortyom; Nicholas Ajegba Abakpa (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
The research explores the effect of enterprise risk management (ERM) on the performance of microfinance institutions in Makurdi Metropolis. The study particularly examines the effect of risk identification, risk assessment and risk mitigation on firm performance. The research employed a survey design. The targeted population consists of 42 management staff of seven microfinance banks within Makurdi Metropolis. The data obtained from the participants via self-administered questionnaire were analyzed with correlation and regression. The outcomes discovered that risk identification, risk assessment and risk mitigation have affirmative and significant effect on the performance of microfinance institutions in Makurdi Metropolis. It concludes that ERM strategies considerably affect the performance of microfinance institutions. The research therefore suggests that microfinance institutions should always evade risks that present superfluous consequences and they should institute plans and actions that will support them to anticipate and circumvent high risk situations.